Celiac Disease in Adult Patients: Specific Autoantibodies in the Diagnosis, Monitoring, and Screening. (3rd April 2014) - Trigoni, Evagelia; Tsirogianni, Alexandra; Pipi, Elena; Mantzaris, Gerassimos; Papasteriades, Chryssa
Abstract : The increasing prevalence of celiac disease (CD), especially in adults, its atypical clinical presentation, and the strict, lifelong adherence to gluten-free diet (GFD) as the only option for healthy state create an imperative need for noninvasive methods that can effectively diagnose CD and monitor GFD. Aim . Evaluation of anti-endomysium (EmA) and anti-tissue transglutaminase IgA (tTG-A) antibodies in CD diagnosis, GFD monitoring, and first degree relatives screening in CD adult patients. Methods . 70 newly diagnosed Greek adult patients, 70 controls, and 47 first degree relatives were tested for the presence of EmA and tTG-A. The CD patients were monitored during a 3-year period. Results . EmA predictive ability for CD diagnosis was slightly better compared to tTG-A (P = 0.043 ). EmA could assess compliance with GFD already from the beginning of the diet, while both EmA and tTG-A had an equal ability to discriminate between strictly and partially compliant patients after the first semester and so on. Screening of first degree relatives resulted in the identification of 2 undiagnosed CD cases. Conclusions . Both EmA and tTG-A are suitable markers in the CD diagnosis, in the screening of CD among first degree relatives, having also an equal performance in the long term monitoring.